Chondrocyte autophagy mechanism and therapeutic prospects in osteoarthritis - Li, Lan; Li, Jie; Li, Jian-Jiang; Zhou, Huan; Zhu, Xing-Wang; Zhang, Ping-Heng; Huang, Bo; Zhao, Wen-Ting; Zhao, Xiao-Feng; Chen, En-Sheng (Frontiers in Cell and Developmental Biology, 2024)
Osteoarthritis (OA) is the most common type of arthritis characterized by progressive cartilage degradation, with its pathogenesis closely related to chondrocyte autophagy. Chondrocytes are the only cells in articular cartilage, and the function of chondrocytes plays a vital role in maintaining articular cartilage homeostasis. Autophagy, an intracellular degradation system that regulates energy metabolism in cells, plays an incredibly important role in OA. During the early stages of OA, autophagy is enhanced in chondrocytes, acting as an adaptive mechanism to protect them from various environmental changes. However, with the progress of OA, chondrocyte autophagy gradually decreases, leading to the accumulation of damaged organelles and macromolecules within the cell, prompting chondrocyte apoptosis. Numerous studies have shown that cartilage degradation is influenced by the senescence and apoptosis of chondrocytes, which are associated with reduced autophagy. The relationship between autophagy, senescence, and apoptosis is complex. While autophagy is generally believed to inhibit cellular senescence and apoptosis to promote cell survival, recent studies have shown that some proteins are degraded by selective autophagy, leading to the secretion of the senescence-associated secretory phenotype (SASP) or increased SA-β-Gal activity in senescent cells within the damaged region of human OA cartilage. Autophagy activation may lead to different outcomes depending on the timing, duration, or type of its activation. Thus, our study explored the complex relationship between chondrocyte autophagy and OA, as well as the related regulatory molecules and signaling pathways, providing new insights for the future development of safe and effective drugs targeting chondrocyte autophagy to improve OA.